Eksplorasi Campur Kode Dalam Interaksi Pelanggan dan Barista di Kopi Kelud Bangkalan - Vanya Dwica Cicilia; Eka Susylowati; Fitriyatuz Zakiyah; Dea Kurnia Sandy (Journal of Social, Culture, and Language, 2024)
Nowadays, a coffee shop on Madura Island has begun to be established with a lot of interesting interiors.There are many ways to develop the coffee shop so that it doesn’t go out of date and remains visited by tourists. One of them is to provide good service by interacting using code-mixing. The purpose of the research is to find out the use of mixed codes used for interaction between customers and baristas in Coffee Kelud Bangkalan. According to Suwito (1985:76), code mixing has two parts: Inner Code Mixing and Outer Code Mixing. This research used qualitative descriptive methods.As for the technique performed by the researchers to collect the data of this research, it is observation or direct observation, recording and taking notes of interactions using code mixing. The source of the data is from the observation site of Coffee Kelud Bangkalan. In this research, five code-mixed events were found in interaction between baristas and customers with the application of outer code mixing, which was characterized by the use of foreign languages, one of which was English. Meanwhile, inner code mixing uses regional languages, namely Madurese. And in one context, it is possible to use hybrid code mixing which is influenced by the difficulty of finding the right match. Keywords: code mixing, coffee shop, Madura island